The effect of Cycoce! and Nitrogen Level on the Growth and Yield of *Sidi Misri 1’ Dwarf Wheat (Triticum aestivum L.) - SOROUR, F. A.; EL-SHARKAWY, M. A. (The Libyan Journal of Agriculture, 2023)
The effect of cycocel and nitrogen level on growth, yield, and yield components of 4Sidi Misri 1’ wheat was studied in a field experiment in the 1973-1974 season at the Faculty of Agriculture Farm, Tripoli, Plant height was increased by increasing the nitrogen level and was decreased by spraying with cycocel. Tillering was not significantly affected by either the nitrogen level or the cycocel treatment. Spike length and peduncle length were increased with the increase in the nitrogen level. On the other hand, spike length was not significantly affected by cycocel treatment, but spike peduncle was decreased with the cycocel treatment. Total dry yield of grain and straw, and straw yield were increased by increasing the nitrogen level, and were not affected by cycocel treatment. The percentage of grain to straw was increased by cycocel spray and was not affected by the nitrogen level. Grain yield per hectare was increased with the increase in the nitrogen level and by spraying cycocel at the rate of 80 kgN/ha. On plant basis the grain weight per plant and per spike was increased with the increasing nitrogen level, but was not affected by cycocel. The number of grains per plant and grain size were not significantly affected by either nitrogen or cycocel treatments.